The Breakup of the Former Socialist Republic of Bosnia and Herzegovina - the Drina Battlefield - Lunić, Tomislav (Napredak, 2023)
We provide the analysis of the war in the former Socialist Republic of Bosnia and Herzegovina by analyzing the Yugoslav crisis, namely, the disintegration of the Socialist Federal Republic of Yugoslavia (SFRY). Bosnia and Herzegovina was located in the heart of the former SFRY. It was a bridge between Croatia and Slovenia in the west and northwest, with Serbia and Macedonia in the east and southeast, and with Montenegro in the south. After Slovenia and Croatia declared their independence, Bosnia and Herzegovina stopped being that "synapse", the solid foundation of unity and coexistence of Serbs, Croats, and Muslims. In 1992, the civil "spilled over" into the Socialist Republic of Bosnia and Herzegovina. The Dayton Agreement ended the war in 1995. To begin with, we describe the events that led to the breakup of the former SFRY. The introduction of the multi-party system and democratic elections in 1990 did not ease the growing tensions. The three constituent nations of Bosnia and Herzegovina could not agree on the constitutional framework of the country they were creating. The Muslims insisted on unitary Bosnia; the Croats supported the union of the three entities, while the Serbs wanted to preserve the Socialist Republic of Bosnia and Herzegovina as a part of the Socialist Federal Republic of Yugoslavia. The plan was to potentially make the country a federation or a confederation. The War was inevitable. In the second part of the paper, we focus on the creation of the Republic Srpska and the Army of the Republic Srpska, with the emphasis on the war events that took place in the Drina area. The Drina River, as a natural border between Serbia and Bosnia and Herzegovina, represents the "lifeblood" of the survival, existence and well-being of the Serbian people in Bosnia and Herzegovina. Hence, the conflicting side tried to occupy that area to sever the ties of the Republic Srpska with the mother country, Serbia. Finally, based on the relevant data and research findings, we give our opinion on the outcome of the war, as well as the consequences for the current and generations to come.
Keywords: Socialist Republic of Bosnia and Herzegovina; Republic Srpska; Dayton Agreement